Automated Breast Volume Scanner, a new automated ultrasonic device, is useful to examine joint injuries in patients with rheumatoid arthritis. Issue 6 (8th September 2015) - Kawashiri, Shin-ya; Suzuki, Takahisa; Nishino, Ayako; Nakashima, Yoshikazu; Horai, Yoshiro; Iwamoto, Naoki; Ichinose, Kunihiro; Tamai, Mami; Nakamura, Hideki; Origuchi, Tomoki; Isomoto, Ichiro; Uetani, Masataka; et al.
Abstract : Objective. To explore the clinical application of automated scanning of wrist and finger joints by an Automated Breast Volume Scanner (ABVS) in patients with rheumatoid arthritis (RA). Methods. A total of 140 metacarpophalangeal (MCP) joints and 28 wrist joints from the 14 active RA patients were examined by both an ABVS system (the ACUSON S2000) from dorsal sites and by conventional ultrasonography (US) from multiple directions on the same day. We used a semiquantitative scale from 0 to 3 of synovial hypertrophy and the presence of bone erosion by grayscale for both methods; the efficacy of the two methods for identifying synovial hypertrophy and bone erosion were evaluated by kappa coefficient. Results. The scanning time of the ABVS was 2 min per patient and that of conventional US was 15 min per patient. The kappa coefficients of synovial hypertrophy in the MCP joints were 0.60 and 0.79 in wrist joints. These values were increased in the joints where synovial hypertrophy was moderate to severe (scores greater than 2). The kappa coefficients for the presence of bone erosion in the MCP joints were 0.74 and 0.93 in wrist joints. Conclusion. The present data showed a substantial agreement between ABVS and conventional US for assessments of the synovial hypertrophy and bone erosion of wrist and finger joints in patients with RA. Since ABVS can scan the wrist and finger joints automatically in a short time, ABVS is a helpful new ultrasonic method to examine joint injuries in patients with RA.